Factors affecting construction productivity: comparative study between worker's nationality - K., Balakrishnan; N.F., Buang; Mohammad Adam, Adman (UMP Press, 2022)
There are many factors that affect construction productivity based on the worker's background. This study assesses the five factors affecting construction productivity at a construction site in Kuala Lumpur within the worker’s nationalities. In 2019, a survey was distributed to a sample of 60 construction workers with various backgrounds. Descriptive analysis shows that respondents are perceived as moderately, that manpower factors (Mean score =2.88, S.D. = 0.54), external factors (Mean score = 3.32, S.D. =0.59), communication factors (Mean score = 3.23, S.D. = 0.63), resources factors (Mean score = 3.31, S.D. = 0.58) and miscellaneous factors (Mean score = 3.29, S.D. = 0.70) affect construction productivity. Moreover, perception of the four factors (manpower, external, communication and resources) affecting construction productivity had a significant difference between Malaysian and non-Malaysian workers (P<0.05). Therefore, advancement should focus on those four factors to nurture better delivery of construction work; thus, increasing the productivity among workers from different nationalities.